Effect of problem-based learning on students’ attitude towards learning physics- a cohort study - Kanyesigye, Stella T.; Uwamahoro, Jean; Kemeza, Imelda (F1000Research, 2022)
Background: Attitude is a learning scale that informs which approach should be used to call students to school. It can be seen a supporting tool that informs teachers, policymakers, and researchers of the needs for raising interest in learning a certain subject, such as physics. This study aimed at determining the effect of problem-based learning on students’ attitude towards learning physics. Methods: The study followed a quantitative approach with a quasi-experimental design employing cross-sectional survey techniques. The participants of the study were 419 13th-grade physics students of the 2020/2021 school year in both Ugandan government and private secondary schools. Among these students, one group was taught using problem-based learning instruction while another group was taught using traditional instruction for 12 weeks. Data were collected using a standardized tool called Views About Science Survey. Using Microsoft Excel 2016 and Statistical Package for Social Scientist version 23.0, descriptive and inferential statistics were used to determine a significant difference between experiment and control groups. Results: It was found that both problem-based learning and traditional instructions caused a statistically significant positive effect on students’ attitudes towards physics. However, the experimental group gained more positive attitude than the control group as they were more inclined towards the expert-like attitude (thinking like a scientist in a domain) than their counterparts due to the problem based learning approach they learned in. Conclusions: Therefore, it was concluded that problem-based learning is a more effective method of teaching physics than traditional methods. Hence, we suggest that secondary school teachers need to adopt the use of problem-based learning in the teaching of science concepts, especially physics.
Keywords: Problem-based learning; Teaching instruction; Attitude; Physics; Expert-like attitude